KORELASI ANTARA KEBIASAAN MEMBACA DENGAN PRESTASI BELAJAR SISWA KELAS IV DI SDN KUIN SELATAN - Rina Fadliah (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2019)
Reading habit is a process of reading activities carried out by someone repeatedly or continuously and it is often or commonly done by each person in daily activities. Learning achievement is the level of success achieved by someone from an activity or business that can provide emotional satisfaction and can be measured with certain tools or tests. This type of research is quantitative descriptive research, especially correlation. This research was conducted at the South Kuin 1 Primary School, Banjarmasin. The object in this study was the correlation between reading habits and student achievement in grade IV of South Kuin 1 Elementary School in Banjarmasin. The subjects in this study were all fourth grade students of Kuin Selatan 1 Primary School Banjarmasin. The population in this study were all students of Class IVA and Class IVB at the South Kuin 1 Elementary School in Banjarmasin. The sampling technique was carried out using the Purposive Sampling technique, based on the technique, it was found out that the samples in this study were the IVB grade students of South Kuin 1 Elementary School in Banjarmasin, totaling 30 people, consisting of 15 male students and 15 female students. Data collection techniques: Data mining tools used in this study were questionnaires and documentation. Data analysis technique: using the Triserial Correlation formula. The results of the study are that there is a significant correlation between reading habits with learning achievement of fourth grade students at the South Kuin 1 Elementary School in Banjarmasin which is shown by the number rch = 0.981 greater than rtable = 0.361 at the significant level of 5% and at the table value = 0.463 at the level significant 1%. It is suggested to the principal, teachers, parents and all parties concerned but none other than the student himself to cultivate reading awareness, which starts from yourself first. Because any idea that involves a lot of people to do something, should start from the initiator itself. Efforts to improve reading habits in children or students, should be given an example of reading first, because it will be a motivation for them.